LITERASI KESEHATAN PENDERITA HIPERTENSI DALAM MELAKSANAKAN KEPATUHAN DIET PADA LANSIA DI TEGALREJO YOGYAKARTA - Tutik Wahyuningsih (STIKes Surya Global Yogyakarta, 2019)
Background: Health literacy has not been known yet in Indonesia, it is quite difficult to translate this term into Indonesian. 7 from 12 sufferers did not apply or go on a hypertension diet because their health literacy was low which ranged from value 1 to 2. Objective: To determine health literacy and compliance with hypertensive diets in elderly people who have hypertension in Tegalrejo Yogyakarta. Methods: This study was a quantitative descriptive study with an observational / survey approach. The study design in this study used a cross sectional design. The population in this study were 135 people, and the number of samples was 101 people. However, because 2 people did not meet the inclusion criteria, they were dropped. Data analysis using PLS by calculating the value of the inner model and outer model. Results: Literacy did not affect on hypertension diet for path coefficient 0.173 with a significance value of p 0.112 (statistical T value 1.591 T table 1.96). The education has an effect on system literacy of 0.461 with a significance value of 0.006 (statistical T value of 2.748 T table of 1.96). Work does not affect on literacy with path coefficient values of 0.044 with a significance value of p of 0.773 (statistical T value of 0.289 T table of 1.96). Conclusion: Education influences toward health literacy because it can affect one's preferences, behavior and lifestyle. There is no influence between work and health literacy in the elderly. There is no influence between health literacy on adherence to the hypertension diet in the elderly in Tegalrejo.